Disclosure of sexual orientation to health professionals in China: results from an online cross‐sectional study. Issue 1 (6th February 2017) - Tang, Weiming; Mao, Jessica; Tang, Songyuan; Liu, Chuncheng; Mollan, Katie; Cao, Bolin; Wong, Terrence; Zhang, Ye; Hudgens, Michael; Qin, Yilu; Han, Larry; Ma, Baoli; et al.
Abstract: Background : Many men who have sex with men (MSM) in China are "in the closet." The low rate of disclosure may impact sexual behaviours, testing for HIV and other sexually transmitted infections (STIs), and diseases transmission. This study examines factors associated with overall sexual orientation disclosure and disclosure to healthcare professionals. Methods : A nationwide cross‐sectional online survey was conducted from September 2014 to October 2014 in China. Participants completed questions covering socio‐demographic information, sexual behaviours, HIV/STI testing history, and self‐reported HIV status. We defined healthcare professional disclosure as disclosing to a doctor or other medical provider. Results : A total of 1819 men started the survey and 1424 (78.3%) completed it. Among the 1424 participants, 62.2% (886/1424) reported overall disclosure, and 16.3% (232/1424) disclosed to healthcare professionals. In multivariate analyses, the odds of sexual orientation disclosure were 56% higher among MSM who used smartphone‐based, sex‐seeking applications [adjusted odds ratio (aOR) = 1.56, 95% CI: 1.25–2.95], but were lower among MSM reporting sex while drunk or recreational drug use. The odds of disclosure to a healthcare professional were greater among MSM who had ever tested for HIV or STIs (aOR = 3.36, 95% CI: 2.50–4.51 for HIV, and aOR = 4.92, 95% CI: 3.47–6.96 for STIs, respectively) or self‐reported as living with HIV (aOR = 1.59, 95% CI: 0.93–2.72). Conclusion : Over 80% of MSM had not disclosed their sexual orientation to health professionals. This low level of disclosure likely represents a major obstacle to serving the unique needs of MSM in clinical settings. Further research and interventions to facilitate MSM sexual orientation disclosure, especially to health professionals, are urgently needed.